1997
DOI: 10.1111/j.1440-1827.1997.tb04508.x
|View full text |Cite
|
Sign up to set email alerts
|

Late onset type I familial amyloidotic polyneuropathy: Presentation of three autopsy cases in comparison with 19 autopsy cases of the ordinary type

Abstract: Clinicopathological features of three autopsy cases of extremely rare late onset type I familial amyloidotic polyneuropathy were presented and compared with 19 autopsy cases of the ordinary type. In the late onset cases, the ages at onset and at death were 27.5 and 24.5 years older, respectively, compared with the ordinary type. Also, duration of the total clinical course from onset to death was 3.7 years less than in the late onset cases. The degree of amyloid deposition was more marked in the heart of the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 15 publications
1
11
3
Order By: Relevance
“…Our present examination revealed significant amyloid deposition in the cardiovascular system, similar to that described in previous autopsy reports of Ser50Arg and Tyr114Cys types of TTR-related FAP [11,12]. The total amount of amyloid in the heart of the present autopsy case was extremely large, compared with that in 20 cases of FAP (ATTR Val30Met) previously reported in our laboratory [9,10]. In the FAP (ATTR Val30Met), amyloid accumulation in the vascular system is predominant around arteries, especially in the adventitia of arterioles, and shows a fine granular pattern.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our present examination revealed significant amyloid deposition in the cardiovascular system, similar to that described in previous autopsy reports of Ser50Arg and Tyr114Cys types of TTR-related FAP [11,12]. The total amount of amyloid in the heart of the present autopsy case was extremely large, compared with that in 20 cases of FAP (ATTR Val30Met) previously reported in our laboratory [9,10]. In the FAP (ATTR Val30Met), amyloid accumulation in the vascular system is predominant around arteries, especially in the adventitia of arterioles, and shows a fine granular pattern.…”
Section: Discussionsupporting
confidence: 86%
“…FAP (ATTR Ser50Ile) patients commonly present with serious heart failure, fatal arrhythmia and cardiac-conduction block; however, peripheral neuropathy is less frequent, as was well documented in previous case studies [4,6,7]. On the basis of clinico-pathological features in autopsy cases of the common FAP (ATTR Val30Met), it was established that the severity of clinical symptoms is closely related to the quantity of amyloid deposited [9,10]. In addition, although there are only a few case reports describing autopsy findings in other types of TTR-related FAP [11,12], the documented findings were limited.…”
Section: Introductionmentioning
confidence: 92%
“…Renal dysfunction and the degree of proteinuria are correlated with heavy amyloid deposition in the glomeruli, arterioles, and medium vessels, but not with deposition in medullary tissues (42). Renal deposition does not parallel that of myelinated nerve fiber loss in the sural nerve, suggesting that evolution and severity of nephropathy are not correlated with the degree of neuropathy (21,44,47).…”
Section: Renal Pathologymentioning
confidence: 92%
“…Postmortem examinations reported that amyloid deposition on the myocardium was localized to the subendocardial area including the conduction system (38). However, it has been recently noted that some FAP patients with Val30Met ATTR who developed the disease at a later age also suffered severe cardiac amyloidosis with congestive heart failure, and most of them originated from nonendemic areas (44)(45)(46): there were more than 50 kindreds with Val30Met ATTR type FAP previously reported from nonendemic areas in Japan (47). It is well known that in this disease the age of onset differs greatly between patients in endemic foci and those in nonendemic areas (39,47): the age of onset in the vast majority of the former patients is the late twenties to early forties, and the early fifties to late sixties in the latter.…”
Section: Hereditary Amyloidosismentioning
confidence: 99%